Інтелектуальна автоматизована система контролю знань студентів вищих навчальних закладів. - I. Katerynchuk; V. Kravchuk; V. Kulyk; R. Rachok (Kherson State University, 2009)
Conception of construction of the intellectual automated systems of evaluation of knowledge's. The offered system foresees the presence of such subsystems: functional subsystem of transformation of information from external representation in intersystem information; subsystems of transformation from intersystem presentation of information in external information; subsystems of representation of knowledge's, which includes the block of forming of results and system of artificial intelligence.